Analisis Pembiayaan Kesehatan Daerah Bersumber Publik: Studi Kasus di Dinas Kesehatan Kabupaten Bogor Tahun 2012, 2013 dan 2014 - Handayani, Tuti; Nadjib, Mardiati (Jurnal Ekonomi Kesehatan Indonesia, 2016)
This study aims to look at the picture of health expenditures in Bogor District Health Office to see the allotment according to the four dimensions of District Health Accounts (DHA) in 2014 to see the trend in 2012 and 2013. This study took data from a secondary data source realization of health spending that was then processed and presented according to the funding source, budget managers, service providers, and programs. The study used a descriptive research design with evaluative approach and was conducted in Bogor District Health Office. Analysis showed that the total health financing in Bogor District Health Department public sources in 2012 amounted to Rp 289.069.378.168 , - in 2013 the number increased to Rp 338 469 794 825 , - and in 2014 that number was dropped to Rp337.451.928.421 , - . The funding in 2012 and 2013 came from the state budget , district budget and provincial budget , whereas in 2014 from the state budget , district budget , provincial budget and other public funds . Judging from its designation , The most dominant spending, in 2012 , is health financing programs spent of 36.29 % , in 2013 also still dominant health financing program , its share reached 40.09 % , and in 2014 expenditure on health financing portion significantly decreased to only 23.69 %, with the largest health spending in 2014 was for program administration and management , that was 30.92 %.